Understanding Complete Pathologic Response in Oesophageal Cancer: Implications for Management and Survival - K. E. O’Sullivan; E. T. Hurley; J. P. Hurley (Gastroenterology Research and Practice)
Despite significant improvement over recent decades, oesophageal cancer survival rates remain poor. Neoadjuvant chemoradiotherapy followed by oesophageal resection is mainstay of therapy for resectable oesophageal tumours. Operative morbidity and mortality associated with oesophagectomy remain high and complications arise in up to 60% of patients. Management strategies have moved towards definitive chemoradiotherapy for a number of tumour sites (head and neck, cervical, and rectal) particularly for squamous pathology. We undertook to perform a review of the current status of morbidity and mortality associated with oesophagectomy, grading systems determining pathologic response, and data from clinical trials managing patients with definitive chemoradiotherapy to inform a discussion on the topic.